2004
DOI: 10.1641/0006-3568(2004)054[0731:pnloer]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Nitrogen Limitation of Ecosystem Responses to Rising Atmospheric Carbon Dioxide

Abstract: A highly controversial issue in global biogeochemistry is the regulation of terrestrial carbon (C) sequestration by soil nitrogen (N) availability. This controversy translates into great uncertainty in predicting future global terrestrial C sequestration. We propose a new framework that centers on the concept of progressive N limitation (PNL) for studying the interactions between C and N in terrestrial ecosystems. In PNL, available soil N becomes increasingly limiting as C and N are sequestered in long-lived p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

47
1,108
4
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,208 publications
(1,168 citation statements)
references
References 61 publications
47
1,108
4
9
Order By: Relevance
“…We hypothesize that decreased photosynthetic capacity observed in our case could be due to severe reduction in plant available nitrogen in this forest stand due to phenomenon known as progressive nitrogen limitation (PNL). PNL develops because elevated CO 2 leads to N immobilization by plants and microbes which deplete soils of N, causing slower rates of N mineralization progressively reducing the mineral N available for plant uptake in the long term (Gill et al, 2002;Zak et al, 2000;Luo et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that decreased photosynthetic capacity observed in our case could be due to severe reduction in plant available nitrogen in this forest stand due to phenomenon known as progressive nitrogen limitation (PNL). PNL develops because elevated CO 2 leads to N immobilization by plants and microbes which deplete soils of N, causing slower rates of N mineralization progressively reducing the mineral N available for plant uptake in the long term (Gill et al, 2002;Zak et al, 2000;Luo et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Fungal communities are well known as decomposers in the ecosystem, by degrading organic matters into biologically available nutrients (26,68,69). Under eCO 2 , both aboveground and belowground plant biomass was stimulated (5-10), providing more organic matters for fungal communities as well as proposing higher demand for biologically available nitrogen (8,(70)(71)(72). Statistical testing suggested significant correlations between the changed network topology and increased soil ammonification rate and plant biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Such responses were closely related with altered soil and plant properties, especially with increased plant biomass and NH 4 ϩ availability in soil, and thus were expected to sustain as long as the plant biomass is stimulated by eCO 2 . However, studies have shown that the microbial decomposition and plant biomass stimulation by eCO 2 were constrained by limited nitrogen availability in natural soil ecosystems (69,71,72). Therefore, the described responses of fungal community to eCO 2 may be subject to change when a new balance between microbial decomposition, plant biomass and nitrogen availability is reached.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the latest versions of ESMs now include N (and a rare few include phosphorus). However, because N is often a limiting nutrient in ecosystems, the focus is on plant response under limited N conditions and on the effects of the progressive N limitation [104] that is expected under elevated CO 2 . Although some models offer prescribed N, more sophisticated ones employ an N pool (bulk or speciated) that is available to both plants and decomposers.…”
Section: Nitrogenmentioning
confidence: 99%